Prvo jugoslovansko leto Slovencev - gospodarski ukrepi, razhajanja in negotovosti - Lazarević, Žarko (Studia Historica Slovenica, 2021)
The discussion deals with economic developments in 1919, the first year of the interwar period and the first Yugoslav year. In the case of the Kingdom of Serbs, Croats and Slovenes, which is the subject of the analysis, the 1919 year was a complex process due to dynamics of transition to and establishment of new state. At the same time, the Habsburg monarchy was still very much alive in its concepts of regulating everyday private, social and economic life. The author analyzes these processes on the example of the eight-hour working day, agrarian reform, nostrification, war loans, currency reform and entrepreneurial practices in 1919.
Keywords: 1919; agrarian reform; agrarna reforma; Avstro-Ogrska; currency reform; economy; ekonomske reforme; gospodarstvo; Habsburg monarchy; Kraljevina SHS; Slovenci; Slovenia; transition; vojna posojila; war loans; Yugoslavia